Dynamic Changes in the Development of the Educational System of Children with Autism Spectrum Disorders in Russia: Results of the 2020 All-Russian Monitoring - A.V. Khaustov; M.A. Schumskih (Аутизм и нарушение развития, 2021)
The results of the 2020 All-Russian Monitoring of the state of education of students with autism spectrum disorders (ASD) are presented. Monitoring held by the Ministry of Education of the Russian Federation in collaboration with the Federal Resource Center for the Organization of Comprehensive Support to Children with Autism Spectrum Disorders of the Moscow State University of Psychology & Education. The total number of students with ASD in 2020 compared to 2019 increased by 43% and amounted to 32,990 individuals. Most children with ASD (69%) are enrolled in primary, basic and secondary general education. The percent of children with ASD attending general education (inclusive) classes using the “Resource Class” model is 7%. Homeschooling students with ASD make up 37% of the total number of students with autism. The problem of human resources, needed to maintain the educa- tion and support for children with ASD remains: 66% of children receive speech therapist services, 55% — a special teacher, 80% of students with ASD receive support from educational psychologists, only 19% of children with autistic disorders are provided with tutor support. In 43 constituent entities of the Russian Federation, 52 regional resource centers have been created